The Role of Sub-District Administrative Organizations in Managing Landslide Problems: A Case Study of Ban Rae Sub-District, Thanto District, Yala Province - อาแซ, นิไอดีลฟิตดตรี; ยานยา , มูฮัมหมัดรอฟี; สาฆอ , ไพศาล; มินทราศักดิ์, นินุสรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to (1) study the role of Ban Rae Subdistrict Administrative Organization, Thanto District, Yala Province, in managing landslide problems; and (2) propose development guidelines and management approaches for landslide issues in Ban Rae Subdistrict, Thanto District, Yala Province, which is a mountainous area at risk of landslides. This study employed a qualitative research methodology. Seven key informants were purposively selected, including the Subdistrict Administrative Organization executives, community leaders, community development officers, and affected residents. The research instrument used for data collection was a semi-structured interview. Data were analyzed using content analysis and categorized into three phases: before the disaster, during the disaster, and after the disaster the findings revealed that the Subdistrict Administrative Organization plays a significant role in assessing risk areas, preparing disaster prevention and mitigation plans, controlling land use, and promoting reforestation. During the disaster phase, the organization coordinates assistance, evacuates residents, and provides initial support. In the post-disaster phase, it undertakes rehabilitation, provides relief assistance, and repairs infrastructure. however, limitations were identified in terms of personnel and equipment readiness. The recommendations from this study include the development of an early warning system, strengthening public knowledge and participation, and integrating cooperation with relevant agencies to enhance efficiency and sustainability in systematic local-level landslide management.